Behaviour of RC columns strengthened with Ultra-High Performance Fiber Reinforced concrete (UHPFRC) under eccentric loading. (15th April 2022) - Elsayed, Mahmoud; Tayeh, Bassam A.; Elmaaty, Mohamed Abou; Aldahshoory, Yomna
Abstract: This paper involves an experimental study of the structural behaviour of RC columns strengthened with ultra-high performance Fiber reinforced concrete (UHPFRC) under eccentric loading. Twelve rectangular concrete columns were tested, each with a cross section of 120 × 150 mm 2 and a clear height of 1000 mm. Different parameters were considered in this study, such as load eccentricity ratio (e/t), thickness of UHPFRC, volume ratio of steel fibers, and strengthening schemes. The test results showed that the UHPFRC is an effective strengthening technique for improving the strength, moment capacity, stiffness, and toughness of RC columns under eccentric loading. The gain in axial load capacity, moment capacity and stiffness is proportional to the thickness of UHPFRC jacket and inversely proportional to the eccentricity ratio. Specifically, the full casting scheme of UHPFRC jacket was more effective than the bonding laminates scheme. Finally, P-M interaction diagrams were developed analytically to predict column strength. The comparisons between the experimental results and analytical calculations revealed that good agreement can be achieved by the analytical model. Highlights: UHPFC technique is effective in strengthening RC columns under eccentric loadings. Full casting with UHPFC jacket schemes is more effective than bonding laminate schemes. UHPFC thickness significantly influences in axial load capacity, moment capacity. Improved roughening of column surface must be ensured for UHPFC jackets. The results obtained from the analytical model are generally consistent with the experimental ones.